2011
DOI: 10.1007/s10706-011-9456-3
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Studies on Chip Formation in Drag-Pick Cutting of Rocks

Abstract: A two dimensional non-linear finite element simulation model has been developed using a mathematical model for progressive rock failure for understanding the mode and sequence of rock failure under a drag pick cutter. Rock cutting simulation has also been done using linear elastic modeling using local stability factor contouring. It has been observed from the simulation results that during negative rake angle cutting the chipping occurs by shear failure of the elements. Whereas, in positive rake angle cutting,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 21 publications
(32 reference statements)
0
8
0
Order By: Relevance
“…When the cutting depth and pulling force were constant, the stress intensity factor increased with the crack length. Therefore, it indicated that the crack would enter into the unstable fracture when the crack was initiated, and the phenomenon could be verified through the reacting force reduction after the peak point [23].…”
Section: Mechanical Analysis Of Rockmentioning
confidence: 93%
“…When the cutting depth and pulling force were constant, the stress intensity factor increased with the crack length. Therefore, it indicated that the crack would enter into the unstable fracture when the crack was initiated, and the phenomenon could be verified through the reacting force reduction after the peak point [23].…”
Section: Mechanical Analysis Of Rockmentioning
confidence: 93%
“…However, crack propagation and chip separation were not obviously. Meanwhile, two-dimensional discrete element method (DEM 2D) method is also poor in simulating chip separation [26,27], although cracks can be obtained. Stavropoulou [28] and Innauratoetal et al [29] employed finite difference method (FDM) to investigate the chip formation in the rock and cutting tool interaction process and the satisfactory results were achieved.…”
Section: Introductionmentioning
confidence: 99%
“…During rock fragmentation, the cutting force is not only affected by friction and cutting speed, but also by mechanical properties of the rock and tool angle [16], [17]. In the process of breaking hard rock, the increase of cutting force is the main cause of tool failure and low cutting efficiency [18]. In addition, The cutting forces and chip morphology were significantly influenced by sliding velocities and cutting depths [19], [20].…”
Section: Introductionmentioning
confidence: 99%